1995
DOI: 10.1288/00005537-199509000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐assisted uvulopalatoplasty for snoring and obstructive sleep apnea: Results in 170 patients

Abstract: Laser-assisted uvulopalatoplasty (LAUP) is a procedure for the treatment of snoring and, possibly, sleep apnea. Between July 1993 and December 1994, the authors prospectively evaluated 541 consecutive patients referred to their teaching hospital for possible LAUP to treat loud, disruptive snoring. Of these patients, 274 (51%) had one or more LAUP treatments. As of January 1995, LAUP treatment courses were completed in 170 patients. In this paper, the authors report preliminary results on the use of LAUP in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 23 publications
6
78
0
3
Order By: Relevance
“…This has also been reported in a polysomnography study fol lowing UPPP where 30% of initial responders had re lapsed to non-responders at the last follow-up approxi mately 2 years after surgery [19], In one study a successful reduction or elimination of snoring following LAUP was found in 68.7% of 170 patients suffering from heavy snoring (n = 105) or OSAS (n = 65) [14], Our patients operated by LUPP were also either heavy snorers or OSAS patients, although the exact numbers in these groups are not known. However, the high scores for morning fatigue and excessive daytime sleepiness preoperatively as seen in figure 2 indicate that most patients probably suffered from upper airway resis tance syndrome or OSAS.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This has also been reported in a polysomnography study fol lowing UPPP where 30% of initial responders had re lapsed to non-responders at the last follow-up approxi mately 2 years after surgery [19], In one study a successful reduction or elimination of snoring following LAUP was found in 68.7% of 170 patients suffering from heavy snoring (n = 105) or OSAS (n = 65) [14], Our patients operated by LUPP were also either heavy snorers or OSAS patients, although the exact numbers in these groups are not known. However, the high scores for morning fatigue and excessive daytime sleepiness preoperatively as seen in figure 2 indicate that most patients probably suffered from upper airway resis tance syndrome or OSAS.…”
Section: Discussionsupporting
confidence: 55%
“…This procedure also includes the use of laser and is called laser-assisted uvulopalatoplasty (LUPP) and was first presented in 1993 [12], However, the technique is unlike the laser-assisted uvulopalatoplasty (LAUP) as de scribed by Kamami [13] and later evaluated by others [14], The technique will therefore be described here. This approach has been inspired by those of Lindholm et al [ 15] and Carenfelt [ 16] and modified by us.…”
Section: Introductionmentioning
confidence: 99%
“…Patients will often desire treatments that appear to be simple or ''cutting edge'' despite a lack of verified clinical efficacy. The incidence of OSA in patients with loud snoring has been identified at 38% [13] to 73% [18]. Our study indicated that 64% of snorers had OSA.…”
Section: Discussionmentioning
confidence: 57%
“…Kamami reported a 77% complete resolution and 23% partial resolution of snoring [11], whereas Krespi reported 86% and 7% for complete and partial resolution, respectively [15]. In the treatment of OSA, Walker et al reported a 48% success rate based on pre-and postoperative PSGs [13]. Mickelson reported a reduction in apnea index (AI) from 19.4 to 4.2 and in RDI from 31.2 to 15.7, with RDI reduced by at least half in 53.8% of his patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the definition of success rate also varied in these studies to include a postoperative reduction in the RDI or AI (Apnea index) by 50% with or without reduction of the AHI to less than 20 per hour. [82][83][84][85][86][87] Saggital mandibular osteotomies are performed to effect anterior mobilisation of the insertion of the tongue at the genioid tubercle and thus enlarge the retrolingual space. There must be a significant antecedent mandibular deficiency and dental malocclusion to permit the requisite degree of anterior movement of the mandible and the mandibular teeth.…”
mentioning
confidence: 99%